2018
DOI: 10.2147/ott.s168045
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapy and next-generation sequencing-based genetic alteration analysis of malignant solitary fibrous tumor of the pleura

Abstract: BackgroundSolitary fibrous tumor of the pleura (SFTP) is a rare pleural neoplasm arising from mesenchymal cells, accounting for <5% of pleural neoplasms. Approximately 10% of cases of SFTP demonstrate malignant potential, leading to local recurrence after radical surgery and subsequent metastasis.MethodsA large malignant-like mass was found in the left thoracic cavity of a 61-year-old woman. Following radical resection of the mass, the patient was diagnosed with malignant SFTP by histologic and immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
1
8
1
Order By: Relevance
“…Total surgical resection is the preferred treatment for HPC ( 12 , 13 ), which is consistent with the conclusion of our analysis. However, massive bleeding during surgery becomes a barrier to total removal.…”
Section: Discussionsupporting
confidence: 92%
“…Total surgical resection is the preferred treatment for HPC ( 12 , 13 ), which is consistent with the conclusion of our analysis. However, massive bleeding during surgery becomes a barrier to total removal.…”
Section: Discussionsupporting
confidence: 92%
“…NAB2-R593W fusion plays a major role in malign PSFT. Meanwhile, FLT1-R593W and KDR-V2971I somatic mutations are proof of the existence of a malignant angiogenetic phenotype [10].…”
Section: Discussionmentioning
confidence: 99%
“…PSFTs are found within the pleura in 57.7% of cases, with the rest (42.3%) being localized extrapleural [8,10]. The World Health Organization (2015) reviewed the classification of pleural tumors from a pathological view and placed them in three categories: mesothelial tumors, mesenchymal tumors, and lympho-proliferative disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The check-valve mechanism may have caused cystic degeneration during the growth of the tumor. On the other hand, it has been reported that genetic alterations analyzed by next-generation sequencing could be involved in malignant transformation in SFTP [ 10 ], and genetic alterations may also be involved in cystic degeneration. To the best of our knowledge, this is the first report of SFTP with cystic degeneration.…”
Section: Discussionmentioning
confidence: 99%